2013
DOI: 10.5851/kosfa.2013.33.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Meat Characteristics between Korean Native Duck and Imported Commercial Duck Raised under Identical Rearing and Feeding Condition

Abstract: This research was conducted to compare the meat characteristics of Korean native duck and imported commercial duck. The Korean native ducks and imported commercial ducks (broiler duck: Grimaud) were raised under identical rearing and feeding conditions for 8 wk and 6 wk, respectively. At the end of the rearing period, ten ducks from each group were slaughtered, and breast and leg meat were obtained 24 h after slaughtering for analyses of meat characteristics. The results showed that the breast of Korean native… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
35
3
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 17 publications
(15 reference statements)
13
35
3
2
Order By: Relevance
“…Breast and thigh had the same b* value and were higher than from leg and fillet in the present study. In agreement with [13] reported higher b* value from breast than from leg (9.15 VS 6.86). In addition [14] reported that breast had b* value 1.89 and leg had b* value 1.50.…”
Section: Colorsupporting
confidence: 89%
See 2 more Smart Citations
“…Breast and thigh had the same b* value and were higher than from leg and fillet in the present study. In agreement with [13] reported higher b* value from breast than from leg (9.15 VS 6.86). In addition [14] reported that breast had b* value 1.89 and leg had b* value 1.50.…”
Section: Colorsupporting
confidence: 89%
“…These authors explained that breast had lower L* value than leg which was probably due to the higher fat content in leg than in breast. In contrast, [13] reported that breast had higher L* value than leg (49.53 VS 47.93).…”
Section: Colormentioning
confidence: 87%
See 1 more Smart Citation
“…Similar results had been discussed previously [21,[33][34][35]. In the same context, feeding food-processing wastes resulted in a valuable improvement in FCR and GH in ducks as similarly indicated previously in ducks [20,21,28,[35][36][37]. This might be due to enhancing the GP and strengthening the immunity as observed by Giri et al [38] by using guava leaves whereas no available data on using GSP in poultry diets were recorded.…”
Section: Gp and Carcass Characteristics Of Muscovy Duckssupporting
confidence: 85%
“…This might be due to enhancing the GP and strengthening the immunity as observed by Giri et al [38] by using guava leaves whereas no available data on using GSP in poultry diets were recorded. GSP contains phenolics, antioxidants and bioactive derivatives, which might improve the metabolism [34,36].…”
Section: Gp and Carcass Characteristics Of Muscovy Ducksmentioning
confidence: 99%